2018
DOI: 10.1007/s00167-018-5221-y
|View full text |Cite
|
Sign up to set email alerts
|

There is a role for allografts in reconstructive surgery of the elbow and forearm

Abstract: Purpose Allografts play an important role in tendon, ligament, and bone reconstruction surgery, particularly when suitable available autologous tissue is limited. Enthusiasm for the use of allografts in reconstructive orthopedic surgery has increased over the past decade, with an increase in allograft use in a variety of procedures. The purpose of this review is to provide an overview of the various applications and indications for the use of allografts in reconstructive surgical procedures of the elbow and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 76 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…Molenaars et al completed a systematic review which highlighted the role of allografts and the propensity to use Achilles tendon allografts in reconstructive surgery involving the elbow. 12 However, it is not without associated risks, including infectious disease transmission, host rejection, and increased cost. 13 , 17 Bennett and Mehlhoff described a technique for triceps reconstruction with Achilles tendon allograft to augment and bridge the triceps tendon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molenaars et al completed a systematic review which highlighted the role of allografts and the propensity to use Achilles tendon allografts in reconstructive surgery involving the elbow. 12 However, it is not without associated risks, including infectious disease transmission, host rejection, and increased cost. 13 , 17 Bennett and Mehlhoff described a technique for triceps reconstruction with Achilles tendon allograft to augment and bridge the triceps tendon.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Case reports have presented alternatives including, autologous semitendinosus, gracillis allograft, and fascia lata grafts. 3 , 7 , 12 , 20 , 21 While these studies have presented alternatives, no study has compared the biomechanical differences specifically in the setting of triceps grafts. In 2010, Petre et al studied the biomechanical properties of an intact triceps tendon and showed a load to failure (LTF) of 1741.1 N (1705.3-1777.5) and liner stiffness (LS) of 83.7 (71.5-96.0), with directly repaired tendons LTF of 317.4 N (304.1-330.7) LS 12.8 (11.5-14.1) and augmented repairs LTF of 593.1 N (573.7-612.6) and LS 24.9 (22.1-27.8).…”
Section: Discussionmentioning
confidence: 99%
“…Second, repair of the bone defect. Conventional treatments for bone defects generally include transplantation of the fibular segment without a blood supply, inlay bone grafting of cancellous bone, autologous bone marrow transplantation, Ilizarov technique ( 9), bony fusion, or allograft bone transplantation (10,11). However, these methods share 1 defect: the bone graft lacks a blood supply.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Tissue defects caused by a variety of injuries, such as trauma, tumor and birth defects, can severely impair patients' daily and social lives. Traditionally, autografts and allografts are good choices for repair of tissue defects; however, both have serious issues, including a limited tissue supply and extra surgical trauma 1,2 . Although artificial material implantation can be an alternative approach, it has unexpected drawbacks, such as immune rejection and inadequate mechanical properties 3,4 .…”
Section: Introductionmentioning
confidence: 99%